DEVELOPMENT OF RESEARCH COMPETENCE OF STUDENTS OF TECHNICAL HIGHER EDUCATION INSTITUTIONS (Intent Research Scientific Journal, 2023)
The article discusses the need and opportunities to address various issues of training, the development of research competencies of students during the educational process in technical higher education institutions. The advantage of the proposed approach is that students can gradually apply theoretical knowledge in the field of science to practice, developing research skills. Skills in developing research competencies are presented. Criteria and indicators of research competence are considered.